In vitro and in vivo effects of selected Malaysian medicinal plant extracts on Toxoplasma gondii - Devanthran, Kumareswaran (2016)
The sporozoan parasite Toxoplasma gondii is tissue parasite commonly causing infection to humans and animals, particularly in the immunocompromised hosts. Latest report stated that approximately one third of the global population has been infected with T. gondii. The World Health Organisation considers toxoplasmosis as one of the major parasitic diseases infecting human in the developing countries. General therapeutic drug for toxoplasmosis is pyrimethamine. Since it presents several adverse side effects, the need to develop new drugs for this condition is critical. The aim of this study is to investigate anti-toxoplasma effect of some selected medicinal plants. Assays were developed to determine the anti-toxoplasma effects in vitro and in vivo. Four medicinal plants have been used, which are Tinospora crispa, Piper sarmentosum, Andrographis paniculata and Curcuma longa. The plants are reputed in traditional medicine for many treatments of diseases. These medicinal plants reported in literature as antimalarial agent, were evaluated for their in vitro cytotoxicity activity against mammalian cell lines, Vero cell line, which was used as host cell in this anti-toxoplasma activity study. Methyl thiazolyl diphenyl tetrazolium (MTT) assay was used to measure in vitro cytotoxicity activity. The cell culture-based assays were performed in this study to evaluate the plant extract and determine their effectiveness in inhibiting the growth of T. gondii in vitro. In in vivo experiment, survival analysis was conducted to estimate the survival time of T. gondii infected mice treated with plant extract. T. gondii brain cysts were inoculated orally in mice. In each study, three groups of mice were assigned to treatment with plant extract prior to T. gondii infection (prophylactic), after infection (therapeutic), or left untreated (infected untreated control). The plant extract effect on toxoplasmosis was evaluated by the assessment of survival rate and brain cyst burden. All four plant extracts were found non toxic towards Vero cells. The IC50 value for all plant ethanolic extracts were above 100μg/ml. The least toxicity was the extract of C. longa followed by T. crispa, P. sarmentosum and A. paniculata. T. gondii tachyzoites was inhibited by plant extracts in Vero cells by concentration-dependent manner. Even at low concentration as at 25μg/ml, T. crispa and P. sarmentosum extract dramatically inhibited T. gondii tachyzoites in Vero cells. T. crispa extract showed the greatest inhibition on T. gondii tachyzoites growth in Vero cells followed by P. sarmentosum, A. paniculata and C. longa. T. crispa and P. sarmentosum extracts were comparable with positive control, clindamycin. T. crispa extract was found as a potent anti-toxoplasma agent followed by P. sarmentosum, A. paniculata and C. longa for both in vitro and in vivo studies. In infection induced by inoculation of cysts of T. gondii, plant extract in prophylactic or therapeutic regimens significantly enhanced protection of infected mice against death. Delayed deaths of treated mice compare to untreated mice were observed throughout the 60 days observation period. The brains of infected mice treated with plant extract prophylactic or therapeutic groups showed low brain cyst burden compared to the infected untreated control. T. crispa and P. sarmentosum extracts reduced the brain cyst count almost to 25% compared to untreated infected mice. These results suggest that all four plant extracts have potent anti-toxoplasma effect against T. gondii especially T. crispa and P. sarmentosum extracts. These plant extracts can be exploited for development of alternative medicine to treat T. gondii infections.